1982
DOI: 10.1002/pen.760221409
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase polymer processing: Controlled‐ingredient‐distribution mixing and its effect on some properties of styrene‐butadiene (SBR)/butadiene‐acrylonitrile copolymer rubber blend compounds

Abstract: The flex‐crack‐growth resistance and oil‐swelling resistance of a styrene‐butadiene (SBR)/butadiene‐acrylonitrile co‐polymer (NBR) rubber blend are studied as a function of the distribution of ingredients in the individual rubber phases. The blends consist of 70:30 weight ratio of SBR:NBR with incorporation of 82.5 phr carbon black and other ingredients via the controlled‐ingredient‐distribution mixing procedure. The results show that flex crack growth is affected by the distribution of carbon black. Better fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…In other literature, there have been few reports on crack generation and development rate; most reports have been on fatigue life. Compared with Lee's investigation, the N4 nanocomposite shown in Figure (b) showed more than twice the cycles with only half the CB content. Han and Han reported that it needed 0.5–1.5 × 10 4 cycles to reach a 3‐mm fatigue crack, but the N series of nanocomposites exhibited 8–27 × 10 4 cycles in this study.…”
Section: Resultsmentioning
confidence: 54%
“…In other literature, there have been few reports on crack generation and development rate; most reports have been on fatigue life. Compared with Lee's investigation, the N4 nanocomposite shown in Figure (b) showed more than twice the cycles with only half the CB content. Han and Han reported that it needed 0.5–1.5 × 10 4 cycles to reach a 3‐mm fatigue crack, but the N series of nanocomposites exhibited 8–27 × 10 4 cycles in this study.…”
Section: Resultsmentioning
confidence: 54%
“…From previous studies [16][17][18][19], it was found that, the oil immersion of rubber/PVC blend compounds, the oil molecules must penetrate in the rubber phase and go around the PVC phase. This is schematically illustrated in Figure 2.…”
Section: Model Of Swelling Of Rubber/pvc Blendsmentioning
confidence: 99%